Evaluation of intra-articular injection of bupivacaine in combination with morphine, methylprednisolone, or alone on pain after knee arthroscopy - Hamid Kayalha; Ali Alizadeh; Hoda Shahamat; Idin Binazadeh; Sharam Rastak; Mohammad Sofiabadi (مجله دانشگاه علوم پزشکی بیرجند, 2020)
Background and Aims: Knee arthroscopy is used to diagnose and treat intra-articular lesions. The control of acute pain after arthroscopy requires the use of a method with the least side effects and most efficacies. This study aimed to compare the sedative effect of bupivacaine in combination with morphine, methylprednisolone, or alone in knee arthroscopy after intra-articular injection. Materials and Methods: This clinical-randomized three-blind trial included 99 volunteer patients with knee arthroscopy. The patients were randomly divided into three groups of bupivacaine (0.5%), morphine (5 mg)+bupivacaine (0.5%), and methylprednisolone (40 mg)+bupivacaine (0.5%). At the end of the surgical operation, the intra-articular injection of the medications were performed, and the amount of postoperative pain was evaluated and recorded based on visual analog scale 6, 12, 18, and 24 h after injection. In addition, the reception of the injected analgesic within 24 h was recorded in this study. Data were analyzed using SPSS software (version 19) through ANOVA. Results: In all three groups, the pain intensity decreased significantly over time. The pain intensity of the methylprednisolone+bupivacaine and morphine+bupivacaine groups was similar at different postoperative periods; however, the pain intensity of these groups was significantly lower than that in the control group. In addition, consumption of the analgesics was significantly reduced in the methylprednisolone+bupivacaine group, compared to the other two groups. Conclusion: The results of this study showed that the intra-articular injection of methylprednisolone+bupivacaine and morphine+bupivacaine was more effective than bupivacaine alone in reduction of pain and the need for injectable analgesia.